Asymptomatic coronavirus disease followed by symptomatic reinfection in a patient with monoclonal gammopathy of undetermined significance: A case report - Varsha Narayanan, (Indian Journal of Case Reports, 2021)
Coronavirus disease (COVID-19) pandemic has been present for over a year and has been seen to behave unpredictably in differentpeople especially those with other underlying health conditions. Monoclonal Gammopathy of Undetermined Significance (MGUS) isa rare condition that can alter immune responses. There are few case reports of COVID in people with MGUS and most of these are inelderly people often with associated comorbidities. The mutual impact of COVID and MGUS in younger people (